Legal Guarantees for the Protection of Public Health Against the Spread of Infectious Diseases - New Challenges and Threats - Czechowicz, Sebastian (Medicine, Law & Society, 2021)
Public health is considered a social value. Effective laws are critical to achieving high levels of public health. The legislature faces many challenges in protecting human life and health. The COVID-19 pandemic is the best evidence of this. Effective prevention of infectious diseases and epidemic threats should not escape the legislature's attention. Both preventive measures and effective fight against already existing threats are essential for their elimination. This work presents the results of research on the doctrine of public health and the legal guarantees of its protection. The paper presents the most recent threats to human life and health associated with the spread of infectious diseases. The paper also presents the results of statistical research on the effectiveness of the fight against the spread of infectious diseases.